Pembelajaran Pendidikan Agama Islam Berbasis Teknologi Dalam Era Digital Untuk Peningkatan Kepribadian Siswa Di SMK Andalusia 1 Wonosobo - Nova Qhorisiatul Zhakira; Salis Irvan Fuadi; Noor Aziz (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Various forms of innovation and creation are needed in the field of education because in order to advance education, it has always undergone metamorphosis over thousands of years. The current behavior of Indonesian students is reflected in their worrying personalities and tends to decline quite sharply. It was found that many students pay little attention to manners and manners, especially when interacting with senior citizens. The aim of this research is to determine the use of technology in Islamic Religious Education in the digital era. to find out more about the character of class XI students at SMK Andalusia 1 Wonosobo. to find out whether digital media-based Islamic Religious Education courses can help class XI Andalusia 1 Wonosobo students become better human beings. The research methodology used in this research is quantitative. Quantitative research methodology refers to a particular type of research that is orderly, systematic, and well structured from the start until the research design is developed. This kind of research requires a lot of calculations, from data collection, interpretation, to presenting the results. Participants in this research were class XI students at SMK Andalusia 1 Wonosobo. At the conclusion of the study, it may be more acceptable to include figures, tables, graphs, or other displays. The research results showed that based on digital era technology and multiple choice questions, the experimental class (AKL1) obtained an average PAI score of 84.5, with the highest score being 90 and the lowest being 71. In contrast, the control group using traditional techniques had an average score 78.8, with the highest score of 87 and the lowest score of 71. The average pretest and posttest scores for PAI learning based on digital era technology in the two classes above show an increase in the average score in the experimental group compared to what happened in the control group. The average learning outcomes are also higher in the experimental class. Class personality comes in second. Third, utilizing technology in the digital era to teach Islamic Religious Education and help students become better humans. It is clear that there is a significant difference between the experimental class and the control class if the significance value is less than 0.05. class post-test results. The analysis findings show that the children's personalities have developed.